Laminin - A Prognostic Marker in Oral Squamous Cell Carcinoma - Dr. Sushanta Kumar Singh,; Dr. Gayatri Rath,; Dr. Ashok Kumar Panda, (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Squamous cell carcinoma is one of the most common malignant tumours of the oral cavity and is the tenth most common cause of death worldwide. Because of the high malignant potentially these cases are detected at an advanced stage. Also the recurrence rate is high which invites challenge to the treating surgeon. Laminin, a basement membrane molecule is a reliable marker to predict dif-ferentiation and aggressiveness of the oral squamous cell carcinomas. Methods: The study was conducted in the department of pathology, S. C B Medical College, Cuttack with an aim to predict the tumour aggressiveness and thereby prognosis. A total number of 76 cases were studied using the laminin immunostaining and the results tabulated and interpreted. Results: Majority were well differentiated squamous cell carcinomas, which showed mild to moderate intra cytoplasmic staining of laminin and an intense staining at the tumour host interface, in contrast to an intense intra cytoplasmic staining in poorly differentiated squamous cell carcinoma cases. Those with lymph node metastasis and involved surgical margins also showed intense intra cytoplasmic laminin staining pointing to a higher grade tumour. Conclusion: Laminin immunostaining is definitely superior to the conventional staining procedures for the as-sessment of tumour aggressiveness and differentiation, intra-operative assessment of tumour excision margins and thus access prognosis. Recent researches highlight on Laminin antibodies, which can be used as specific chemotherapeutic agents, to check the process of tumour growth and invasion.